Spectroscopic Studies of Fermi LAT Blazars - Saario, Joonas (fi=Turun yliopisto|en=University of Turku|, 2016)
Blazar research offers a view to one of the most energetic physical processes known to man. The high-energy end of blazar emission has been probed by the Fermi satellite mission since 2008, and it has catalogued more than a thousand gamma- ray bright blazars. However, a large fraction of these sources have no spectroscopic classification at lower energies. In this thesis, optical spectra for sixteen Fermi blazar candidates are published. The optical spectroscopic data have been observed with the Nordic Optical Telescope on the island of La Palma, Spain, during the summer of 2015. The ALFOSC instrument was used, with exposure times from 800 to 3000 seconds per target, yielding signal- to-noise ratios from 10 to 38. All of the sixteen targets show a flat, featureless optical spectrum, characteristic to BL Lacertae objects. The spectra of two targets contain faint emission features, and faint absorption features are seen in three targets. However, none of the features could be reliably identified. Therefore all of the targets are classified as BL Lacertae objects. This classification is supported by the statistical distribution of Fermi -selected active galactic nuclei; more than half of the identified Fermi AGN are BL Lacs. However, the classification of this sample could be improved further with a new observing campaign. This is especially true for the objects with uncertain spectral features.